Mengapa Memilih Bank Syariah? (Sebuah Kajian Dari Persepsi Nasabah Non-Muslim) - Nurlinda; Zuhirsyan, Muhammad (Politeknik Cendana, 2020)
The purpose of this study is to analyze and find the point of view of non-Muslim customers when choosing Islamic banking. This research is a qualitative study using open and closed interviews in collecting data. The data analysis technique used descriptive analysis. The results showed that there is interest from non-Muslim customers in Islamic banking, especially interest in choosing financing products. Interest in choosing Islamic banking from non-Muslim customers is determined by the perception of the benefits obtained, the ease of installment arrears, and the low cost of capital. Meanwhile, the main reasons for non-Muslim customers are not interested in Islamic banking products are because of the confusing and unclear terms, unclear calculation methods, and lack of literacy about Islamic banking among non-Muslim communities.